1995
DOI: 10.1111/j.1439-0442.1995.tb00404.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and Radiological Investigations on Osteochondrosis in Pigs, Associated with Leg Weakness

Abstract: Summary Two‐hundred and seventy‐eight Danish Landrace boars were examined radiologically and pathologically for osteochondrosis and other joint lesions on the left legs at slaughter (95 kg). The joint changes were scored on a scale from 1 (normal) to 5 (very severe changes/osteochondritis dissecans). The correlations between radiological and pathological scores were highly significant in the humeral condyles (r = 0.66, P < 0.001), the distal ulna growth plate (r = 0.51, P < 0.001), the femoral condyles (r = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
63
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 17 publications
11
63
3
Order By: Relevance
“…In general, our results agree with results by Jørgensen (2000) and Jørgensen et al (1995). Those authors also found slight phenotypic associations between several leg weakness symptoms and pathological changes of bones and joints.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In general, our results agree with results by Jørgensen (2000) and Jørgensen et al (1995). Those authors also found slight phenotypic associations between several leg weakness symptoms and pathological changes of bones and joints.…”
Section: Resultssupporting
confidence: 93%
“…Those authors used a sub-data set of this study that included only test animals slaughtered in 2002 and 2003. Jørgensen et al (1995) observed a higher prevalence and variation of subchondral lesions at the medial humeral and femoral condyles in Danish Landrace boars. The prevalence at the lateral humeral condyles was similar to the present study and osteochondral lesions at the distal ulna growth plate showed the most phenotypic variation also.…”
Section: Resultsmentioning
confidence: 75%
“…Thus, it would be expected that depression of the edge of the radius and irregular sagittal groove were less closely associated with the other four lesions than these were with each other. With the exception of the studies by Jørgensen and co-authors (Jørgensen, 1995;Jørgensen et al, 1995;Jørgensen and Nielsen, 2005), other studies of osteochondrosis in the elbow generally do not describe the degree of the depression of the proximal edge of the radius or the degree of irregularity of the sagittal central groove. Consequently, the significance of these lesions in the osteochondrosis complex has been less well established.…”
Section: Discussionmentioning
confidence: 99%
“…The welfare consequences of osteochondrosis in pigs are not well understood. Only weak associations between the presence of osteochondrosis and clinical signs have been established (Grøndalen, 1974;Goedegebuure et al, 1988;Jørgensen et al, 1995). Severe cases of osteochondrosis in the elbow have been found to be associated with stiff gait and forelegs turned outwards Jørgensen, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation